1997
DOI: 10.1128/aem.63.6.2166-2174.1997
|View full text |Cite
|
Sign up to set email alerts
|

Laccase isoenzymes of Pleurotus eryngii: characterization, catalytic properties, and participation in activation of molecular oxygen and Mn2+ oxidation

Abstract: Two laccase isoenzymes produced by Pleurotus eryngii were purified to electrophoretic homogeneity (42-and 43-fold) with an overall yield of 56.3%. Laccases I and II from this fungus are monomeric glycoproteins with 7 and 1% carbohydrate content, molecular masses (by sodium dodecyl sulfate-polyacrylamide gel electrophoresis) of 65 and 61 kDa, and pIs of 4.1 and 4.2, respectively. The highest rate of 2,2-azino-bis(3-ethylbenzothiazoline-6-sulfonate) oxidation for laccase I was reached at 65°C and pH 4, and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
1
7

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(75 citation statements)
references
References 63 publications
(59 reference statements)
6
61
1
7
Order By: Relevance
“…The pI of P. tephropora laccase (pH 3AE3) was in the acidic range reported for laccases from other white rot fungi, such as Pleurotus eryngii and Pleurotus ostreatus (pI 2AE9-4AE7) (Palmieri et al 1993;Muñoz et al 1997), Coriolopsis rigida (Saparrat et al 2002) Pycnoporus cinnabarinus (pI 3AE7) (Eggert et al 1996).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The pI of P. tephropora laccase (pH 3AE3) was in the acidic range reported for laccases from other white rot fungi, such as Pleurotus eryngii and Pleurotus ostreatus (pI 2AE9-4AE7) (Palmieri et al 1993;Muñoz et al 1997), Coriolopsis rigida (Saparrat et al 2002) Pycnoporus cinnabarinus (pI 3AE7) (Eggert et al 1996).…”
Section: Discussionmentioning
confidence: 72%
“…Indeed, there was a factor of specificity of 17 between this substrate and 2,6-DMP. Fungal laccases are known to possess a very wide range of substrate affinities (Mayer 1987;Eggert et al 1997) and even the laccase isozymes of the same strain may also show differential substrate affinities (Fukushima and Kirk 1995;Muñoz et al 1997). The effects of several laccase inhibitors were determined with 2,6-DMP (5 mmol l )1 ) as a substrate in 100 mmol l )1 sodium acetate buffer (pH 4AE0).…”
Section: Substrate Specificity and Inhibition Patternmentioning
confidence: 99%
“…The molecular mass of the native protein was estimated to be 73 kDa by gel permeation chromatography (data not shown) and 70 kDa based on SDS-PAGE ( Fig. 1), indicating its monomeric nature like the P. eryngii laccase (MUNOZ et al 1997). Isoelectric focusing of L 2 of P. florida showed homogeneous protein band with a pI value of 4.2 (data not shown).…”
Section: Resultsmentioning
confidence: 94%
“…A number of laccase isozymes have been isolated and purified from Pleurotus spp. (MUNOZ et al 1997, PALMIERI et al 1993, SANNIA et al 1986, RESCIGNO et al 1993, YOUN et al 1995 but role of these enzyme in producer organisms has not yet been reported. Pleurotus florida produces two extracellular laccase isozymes (L 1 and L 2 ) and involvement of L 2 in the regulation of mycelial growth and yield of the mushroom has been suggested (DAS et al 1997).…”
mentioning
confidence: 99%
“…This cleavage of different covalent bonds formed within lignin macromolecules and between lignin and structural sugars open up the biomass structure, leading to increased availability of easily degradable sugars by microbes. The laccase enzyme is stable over a wide range of pH and temperatures (Baldrian, 2006;Munoz et al, 1997;Stoilova et al, 2010;Thurston, 1994). By using laccase enzyme, the rate of thatch decomposition can be improved over a wide range of environmental conditions by enhancing microbial decomposition of easily decomposable cellulose and hemicellulose.…”
Section: Use Of Laccase Application To Manage Thatchmentioning
confidence: 99%